Kandungan Logam Berat Timah Hitam (Pb) dalam Urine Siswa Sekolah Dasar - Zunidra Zunidra (Journal of Telenursing (JOTING), 2022)
This study aims to determine the content of heavy metal lead (Pb) in the urine of elementary school (SD) students in Jambi City. The method used is a descriptive survey involving elementary school students near the highway with inclusion criteria, namely elementary school students in grades 2-6 and the distance from elementary school to the highway is less than 50 meters. The levels of lead in students' urine were measured using the Atomic Absorption Spectrometer (AAS). The results showed that the Pb content in the students' urine ranged from 0.024 ppm - 0.068 ppm. The highest level of vehicle density at SDN Jambi City adjacent to the highway is 1,520 vehicles/hour. In conclusion, the urine of elementary school students has lead levels that exceed the required limits, so it can be dangerous if left for a long time. Keywords: Heavy Metals, Students, Lead, Urine